2020
DOI: 10.3390/jcm9061779
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Foot Infections: The Diagnostic Challenges

Abstract: Diabetic foot infections (DFIs) are severe complications of long-standing diabetes, and they represent a diagnostic challenge, since the differentiation between osteomyelitis (OM), soft tissue infection (STI), and Charcot’s osteoarthropathy is very difficult to achieve. Nevertheless, such differential diagnosis is mandatory in order to plan the most appropriate treatment for the patient. The isolation of the pathogen from bone or soft tissues is still the gold standard for diagnosis; however, it would be desir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 96 publications
(153 reference statements)
0
41
0
7
Order By: Relevance
“…Patients usually need to be hospitalised for a long time or repeatedly in a specific period of time because of the symptom exacerbations; additionally, they need to take long-term medications for diabetes and complications. The treatment of infections in DFU should be done after identification of the pathogen and analysing the susceptibility to antibiotics, and a correct diagnostic is established [51,52]. Costs related to microbiological testing are variable with the method used, confirmation of a strain with a resistance phenotype, therapeutic options, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Patients usually need to be hospitalised for a long time or repeatedly in a specific period of time because of the symptom exacerbations; additionally, they need to take long-term medications for diabetes and complications. The treatment of infections in DFU should be done after identification of the pathogen and analysing the susceptibility to antibiotics, and a correct diagnostic is established [51,52]. Costs related to microbiological testing are variable with the method used, confirmation of a strain with a resistance phenotype, therapeutic options, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Charcot osteoarthropathy, with or without a superimposed infection, is another foot complication of diabetes that further complicates the diagnosis. Indeed, the most important diagnostic challenge is to differentiate between these three conditions since they require very different therapeutic approaches [17]. In case of OM, it is also important to correctly evaluate the extent of the infection and of affected bones.…”
Section: Role Of [ 18 F]fdg Pet/ct In Diabetic Foot Infectionsmentioning
confidence: 99%
“…Plain X-ray film usually represents the first step imaging modality since it provides an anatomical overview of the foot and detects any pre-existing condition that should be known for the correct interpretation of second level imaging modalities. Despite the specificity for detecting an infection is low, MRI is the radiologic modality of choice for the study of DFI since it provides high quality images with high definition between soft tissues and bone, being able to achieve the diagnosis of infection with a good accuracy [17]. From a nuclear medicine point of view, the gold standard imaging modality for diagnosis of infective complications of DF, still remains radiolabeled white blood cell (WBC) scintigraphy [20][21][22][23], especially if performed following EANM recommendations [20,24,25], as also demonstrated in previous meta-analysis [26] and by a large retrospective study comparing radiolabeled WBC scintigraphy, [ 18 F]FDG PET/CT and MRI [23].…”
Section: Role Of [ 18 F]fdg Pet/ct In Diabetic Foot Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…35 They found that although blood cell scintigraphy appears to be the most reliable imaging modality for differentiating osteomyelitis, soft tissue infection, and Charcot in patients with suspected DFI, both FDG and WBC have significantly higher specificity than MRI. 28…”
Section: Comparison With Wbc Scintigraphymentioning
confidence: 99%